Livestock: A Search for Viable Strategic Option for Poverty Alleviation in Nepal - Luitel, Chakrapani (Economic Journal of Nepal, 2006)
Poverty is an important issue for Nepalese development process. Various plans have been implemented for reducing the poverty. Government received huge amount of foreign aid from donors in the name of the poverty alleviation program. But the result is still less than need and expectations. In reality, poverty alleviation requires resources mobilisation, which is available to poor. Livestock in the rural area is important resource in the Nepalese economy and attached with economy and human life in various ways. Most of the farmers have kept number of domestic animals integrating with the agriculture. It is widely accepted in most of the communities. The climatic variation also provides opportunities to all people of different ecological belts. It is considered as the important resource for producing foods, generating income and employment in all areas. In addition to direct production, livestock sector helps to promote the other economic activities and support of day-to-day life of the people. The development of the livestock sector would be helpful to affect the life of all people so that poverty alleviation would be possible. Economic Journal of Nepal Vol.29(2) 2006 pp.108-124